The relations between Islam and secularism: the impact of social behavior in Turkey - Ismail, Nik Ahmad Hisham; Teke, Mustafa (Canadian Center of Science and Education, 2016)
Secularism as central to society and human life may bring undesired negative consequences in Muslim societies. Increasing social problems among juveniles in Turkey raised questions regarding the right personality development and education of young people. In extending further analysis, we conducted semi-structured interview with experts to assess the level of Turkish personality and impact of Said Nursi, who is a very influential Islamic scholar in Turkish society and to the Islamic movement in general. This study implies that education integrated with Islamic belief and practice will be more influential to educate Turkish Muslims, rather than secular based teaching. This result will be a guideline for educationists and counselors. In future study, developing a personality scale integrated with belief and practice will be beneficial to Muslim communities.